2008
DOI: 10.1111/j.1540-5885.2008.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing Supplier Involvement in New Product Development: A Multiple‐Case Study*

Abstract: Existing studies of supplier involvement in new product development have mainly focused on project-related short-term processes and success factors. This study validates and extends an existing exploratory framework, which comprises both long-term strategic processes and short-term operational processes that are related to supplier involvement. The empirical validation is based on a multiple-case study of supplier collaborations at a manufacturer in the copier and printer industry. The analysis of eight cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
245
2
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(270 citation statements)
references
References 51 publications
10
245
2
13
Order By: Relevance
“…In technologically uncertain projects, purchasing's role seems to be limited to transactional issues. This contrasts with previous studies that have suggested that purchasing has an increased role in coordinating cross-functional and relational responsibilities in NPD (McGinnis & Vallopra 1999;Schiele 2010;van Echtelt, et al 2008). We propose that purchasing enables transactional but not necessarily relational governance with suppliers, at least in situations of technological uncertainty.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In technologically uncertain projects, purchasing's role seems to be limited to transactional issues. This contrasts with previous studies that have suggested that purchasing has an increased role in coordinating cross-functional and relational responsibilities in NPD (McGinnis & Vallopra 1999;Schiele 2010;van Echtelt, et al 2008). We propose that purchasing enables transactional but not necessarily relational governance with suppliers, at least in situations of technological uncertainty.…”
Section: Discussioncontrasting
confidence: 89%
“…In this paper we suggest that they may fulfill different roles in achieving responses building on limiting and increased level of collaboration as proposed in proposition 1. This leads to the following proposition: The organization of governance is not trivial in organizations, and it has been argued that purchasing, together with R&D and production, fulfils an important role in the coordination of the NPD (van Echtelt, et al 2008). With the growing realization that purchasing has a significant influence on a firm's bottom line, scholars have argued that purchasing has an important and maybe even dominant role in transactional as well as relational governance.…”
Section: Transactional and Relational Governancementioning
confidence: 99%
“…While some studies have used the two terms interchangeably, other studies make a clear distinction between them. In such literature, supplier involvement is commonly defined as referring to "the resources (capabilities, investments, information, knowledge, ideas) that suppliers provide, the tasks they carry out and the responsibilities they assume regarding the development of a part, process or service for the benefit of a buyer's current or future product development projects" (Van Echtelt et al, 2008). On the other hand, supplier collaboration is defined as "a type of cross-organizational linkage, which in addition to high levels of integration is characterized by high levels of transparency, mindfulness, and synergies in participants' interactions" (Emden et al, 2006).…”
Section: Supplier Collaboration In Npdmentioning
confidence: 99%
“…Wagner [24] defines supplier integration in new product development as "the combination of internal resources of the buying firm with the resources and capabilities of selected key suppliers through the meshing of intercompany business processes to achieve a competitive advantage". Van Echteltetal [25] provides the following definition: "the resources (capabilities, investments, information, knowledge, ideas) that suppliers provide, the tasks they carry out and the responsibilities they assume regarding the development of a part, process or service for the benefit of a buyer's current or future product development projects. "…”
Section: Supplier Involvement In New Product Developmentmentioning
confidence: 99%